A Disulfide Intercalator Toolbox for the Site‐Directed Modification of Polypeptides. Issue 1 (30th October 2014) - Wang, Tao; Wu, Yuzhou; Kuan, Seah Ling; Dumele, Oliver; Lamla, Markus; Ng, David Y. W.; Arzt, Matthias; Thomas, Jessica; Mueller , Jan O.; Barner‐Kowollik , Christopher; Weil, Tanja
Abstract A disulfide intercalator toolbox was developed for site‐specific attachment of a broad variety of functional groups to proteins or peptides under mild, physiological conditions. The peptide hormone somatostatin (SST) served as model compound for intercalation into the available disulfide functionalization schemes starting from the intercalator or the reactive SST precursor before or after bioconjugation. A tetrazole–SST derivative was obtained that undergoes photoinduced cycloaddition in mammalian cells, which was monitored by live‐cell imaging.